PSII-8 Different nutritional management strategies post-weaning in growth and reproductive performance of Nellore heifers. (30th November 2020) - Araújo, Laylles C; Prados, Laura F; Moriel, Philipe; Vasconcelos, José Luiz M; Resende, Flávio D; Siqueira, Gustavo R
Abstract: The objective of this study was to evaluate different nutritional management strategies (drylot vs. supplementation on pasture) to optimize growth and reproductive performance of Nellore heifers submitted to the fixed-time artificial insemination (FTAI) at 14–15 mo. On d0, 126 weaned Nellore heifers (152±22 kg of BW; 240±28 days of age) were stratified by BW and age, and randomly assigned to receive: (1) high-concentrate-based diet (62.2% TDN, 12.0% CP of DM of diet) ad libitum in feedlot from d 0 to 246 (FDL; 6 pens and 7 heifers/pen); (2) fixed supplementation at 1% of BW on Brachiaria pastures from d0 to 246 (PAS10; 6 pastures; 7 heifers/pastures and 4 ha/pasture); and (3) increasing supplementation on Brachiaria pastures at 0.8% of BW from d 0 to 80 and 1.2% of BW from d 81 to 246 (PAS812; 6 pastures; 7 heifers/pastures and 4 ha/pasture). Supplement offered to heifers on pasture consisted of corn, soybean meal, urea, and minerals (78% TDN, 22% CP of DM at dry season and 79% TDN, 20% CP of DM at rainy season). Final pregnancy rate was determined on d238. Heifer BW on d160 was greater (P < 0.01) for FDL vs. PAS10 and PAS812 (264 vs. 251 and 253±10.1 kg, respectively). Overall ADG from d0 to the start of breeding season (d160) and BW on d246 were greater (P < 0.01) for FDL vs. PAS10 and PAS812 (0.72 vs. 0.62 and 0.64±0.02 kg/d, and 325 vs. 310 and 316 ±10.3 kg, respectively). Heifer BW on d160 and 246 and ADG from d0 to 160 did not differ between PAS10 and PAS812 (P ≥ 0.33). Final pregnancy rates did not differ (P = 0.75) among treatments. Therefore, growth performance, but not pregnancy rates following FTAI, was enhanced for Nellore heifers developed in drylot vs. pasture systems and submitted to FTAI at 14–15 mo.